Implementation of Suspects' Rights as an Embodiment of the Presumption of Innocence Principle in the Examination Process at the Investigation Level - Surdan, Sumianti; Assaad, Andi Istiqlal; Putera, Airlangga (Faculty of Law, Universitas Muslim Indonesia, 2024)
This study aims to find out and analyze the implementation of the rights of suspects as a manifestation of the principle of presumption of innocence in the examination process at the investigation level and to find out the factors that hinder the investigator in the implementation and analyze the rights of suspects as a manifestation of the principle of presumption of innocence at the examination process at the investigation level. This study used the Empirical Law research method, with interviews with related samples/respondents. The source of this research data is to the investigators of the Makassar City Police and some of the rights of suspects as a manifestation of the principle of presumption of innocence in the examination process at the level of investigation of victims of abuse. The results of this study The factors that caused the suspect not to get his rights in the investigation process were the lack of communication between the investigator and the suspect regarding the rights of the suspect contained in the Criminal Procedure Code, in the investigation process the suspect refused to get legal assistance because he was afraid and unable to pay legal counsel even though it was known that there was a right to get legal assistance free of charge. Abstrak Penelitian ini bertujuan Untuk mengetahui dan menganalisis implementasi hak-hak tersangka sebagai perwujudan asas praduga tak bersalah dalam proses pemeriksaan ditingkat penyidikan dan Untuk mengetahui faktor-faktor yang menjadi hambatan penyidik dalam implementasi dan menganalisis hak-hak tersangka sebagai perwujudan asas praduga tak bersalah pada proses pemeriksaan ditingkat penyidikan.Penelitian ini menggunakan metode penelitian Hukum Empiris, dengan wawancara terhadap sampel/responden terkait. Adapun sumber data penelitian ini adalah kepada pihak penyidik Polrestabes Kota Makassar serta beberapa hak-hak tersangka seabagai perwujudan asas praduga tak bersalah dalam proses pemeriksaan ditingkat penyidikan korban penganiayaan. Hasil penelitian ini Faktor-faktor yang menyebabkan sehingga tersangka tidak mendapatkan haknya dalam proses penyidikan kurangnya komunikasi pihak penyidik dengan tersangka mengenai hak-hak tersangka yang terdapat di dalam KUHAP, pada proses penyidikan tersangka menolak untuk mendapatkan bantuan hukum karena takut dan tidak mampu untuk membayar penasehat hukum padahal diketahui bahwa ada hak mendapatkan bantuan hukum secara cuma-cuma.